Risk Assessment Model of Ship Accidents Using Fault Tree Analysis (FTA) Based on Incident Categories and Fatality Factors - Dwi Haryanto (International Journal of Marine Engineering Innovation and Research, 2026)
Maritime transportation plays a vital role in supporting economic activities and regional connectivity in archipelagic countries such as Indonesia yet ship accidents remain a persistent safety concern particularly when they result in loss of life. This study aims to develop a severity oriented risk assessment model for ship accidents by integrating accident categories and fatality factors using Fault Tree Analysis. The study focuses on identifying dominant causal pathways and critical contributing factors that lead to fatal ship accidents rather than merely examining accident frequency. The research adopts a quantitative analytical design using secondary data obtained from 50 officially documented ship accident cases involving fatalities in Indonesian waters between 2017 and 2022. The dataset includes detailed information on accident categories vessel characteristics and causes of death with a total of 295 recorded fatalities. Fault Tree Analysis is applied to structure the causal relationships between basic events intermediate accident categories and the top event defined as a fatal ship accident. Qualitative analysis is conducted to identify dominant failure pathways and minimal cut sets while quantitative analysis estimates the probability contribution of each basic event based on historical fatality data. The results indicate that sinking and fire accidents are the most critical intermediate events accounting for more than three quarters of total fatalities. At the basic event level human related factors dominate fatal outcomes particularly insufficient access to life saving appliances and ineffective emergency response which together contribute more than half of all fatalities. Technical factors such as fire system failure and toxic gas exposure represent the second most significant contributors while environmental and external factors mainly act as amplifiers that reduce survivability after an accident occurs. The integrated qualitative and quantitative analysis reveals that fatal ship accidents are largely driven by dominant high impact basic events rather than complex combinations of multiple low probability failures. This study contributes to maritime safety research by providing an empirically grounded Fault Tree Analysis model that explicitly links accident categories with fatality mechanisms. The findings offer practical implications for risk based maritime safety management by prioritizing human centered interventions emergency preparedness and fire safety systems. The proposed model provides a robust analytical foundation for policy formulation targeted risk mitigation and future development of life safety oriented maritime risk assessment frameworks.